Relasi Perubahan Bentuk, Makna dan Fungsi Ruang pada Rumah Abdi Dalem di Yogyakarta: Studi Kasus: Rumah Abdi Dalem di Kampung Siliran, Kelurahan Panembahan, Kemantren Keraton, Kota Yogyakarta - I Wayan Sutasoma; Paulus Bawole; Freddy Marihot Rotua Nainggolan; Wiyatiningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: The Relationship of Changes in The Form, Meaning, and Function of House Space in The Abdi Dalem Houses in Yogyakarta; Case Study: Abdi Dalem's House in Kampug Siliran, Kelurahan Panembahan, Kemantren Keraton, Yogyakarta City The Yogyakarta City Fort is one of the iconic architectural objects in the Yogyakarta Palace area. Within the fort are several traditional Kampung Abdi Dalem settlements; this residential area is often known as the Jeron Benteng area. Changes in the spatial layout of traditional village houses occur every period. Therefore, this study focuses on the relationship between changes in the form, meaning, and function of the house space in the Kampung Abdi Dalem Siliran settlement, Yogyakarta. The house's occupant is abdi dalem, who serves the Sultan's family. Cultural shifts due to globalization have caused changes in the function, meaning, and form of the house. The leading cause of the changes is the increase in family members and life-supporting activities such as economic and educational endeavors. This study aims to determine the characteristics of changes in the abdi dalem house in Kampung Siliran. The research approach uses qualitative research with case studies. Primary and secondary data were collected through interviews, observations, and documentation. The data were then analyzed and tested for validity using the theory of spatial change flexibility. By analyzing changes in spatial layout, it is concluded that changes in the spatial layout of the abdi dalem house in Siliran Village did not change the main room, but only the additional rooms.